MicroRNA-4639 Is a Regulator of DJ-1 Expression and a Potential Early Diagnostic Marker for Parkinson’s Disease - Chen, Yimeng; Gao, Chao; Sun, Qian; Pan, Hong; Huang, Pei; Ding, Jianqing; Chen, Shengdi (Frontiers in Aging Neuroscience, 2017)
Parkinson's disease (PD) is the second most common neurodegenerative disorder and has profound impacts on the daily lives of patients. However, there is a lack of effective biomarkers for early diagnosis, and the mechanisms of PD pathogenesis remain obscure. microRNAs (miRNAs) are post-transcriptional gene regulators and can be easily detected in plasma, which suggests a promising role as diagnostic markers. Here, we aimed to explore a peripheral biomarker, which not only can be applied for early diagnosis of PD but also has the potential to be a therapeutic target. Through miRNA microarray screening and further validation in plasma from 169 sporadic PD patients, 170 healthy controls, and 60 essential tremor patients, hsa-miR-4639-5p level was identified to be significantly up-regulated in PD patients. Also, it was able to discriminate between early PD patients (disease duration ≤ 2 years or Hoehn & Yahr stage 1-2.5) and healthy controls. Furthermore, hsa-miR-4639-5p was shown to negatively regulate DJ-1 (PARK7), a well-known PD-related gene, in the post-transcriptional level. Abnormal up-regulation of hsa-miR-4639-5p caused down-regulation of DJ-1 protein level, leading to severe oxidative stress and neuronal death. In conclusion, hsa-miR-4639-5p has the potential to be a peripheral diagnostic biomarker and therapeutic target for early PD.